Probiótico líquido para leitões lactentes em diferentes idades - Corrêa, Valney Souza (2008)
The experiment was conducted in Unit Production of Piglets located in the Middle northern state of Mato Grosso, to evaluate the effect of oral administration of probiotic líqüid composed of Lactobacillus reuteri (1.5 x 109 UFC / g) and Bifidobacterium pseudolongum ( 1.5 x 109 UFC / g) in different ages of piglets, the rate of weaning, mortality, weight gain, consumption of feed, occurrence of diarrhea, fecal microbiotic and at the stage of lactation. It was used a completely randomized design with six treatments and six repetitions, and for the microbiota fecal were three replicates. Treatments consisted of: control; oral administration of chemotherapy (in the first and third day of life); probiotic before intake of colostrum; probiotic six hours after ingestion of colostrum; probiotic to three days old; probiotic to 10 days of age. There was no significant difference between treatments in the number of weaners and mortality rate. The administration of probiotic before receiving the colostrum and six hours post-colostrum provided greater consumption of feed at the stage of lactation and greater weight gain in weaning (P <0.05). In the assessment of the occurrence of diarrhea, there was no significant difference between treatments. The microbiological evaluation to seven days of age showed no significant difference (p> 0.05) between treatments. At fourteen days, the piglets who received probiotic before the colostrum and probiotic to 10 days old, showed a higher concentration of Clostridium perfringens (p <0.05). The pigs that received the probiotic three days of age had lower concentrations of Lactobacillus. There was no significant difference (p <0.05) between treatments with respect concentrations of Enterobacteriaceae and total anaerobic bacteria.